SAT0390 Differential FDG-PET/CT findings for spondylarthropathies, PMR, and RA. (23rd January 2014) - Yamashita, H.; Takahashi, Y.; Kaneko, H.; Kubota, K.; Kano, T.; Mimori, A.
Abstract : Objectives: We assessed similarities and differences in fluorine-18 ( 18 F)-labelled fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) findings in patients with seronegative spondyloarthropathy (SpA), polymyalgia rheumatica (PMR), and rheumatoid arthritis (RA). Methods: This study included 51 patients with SpA ( n =19), PMR ( n =16), or RA ( n =16) who were admitted to our hospital between 2006 and 2011. Disease activities in the ischial tuberosities, greater trochanters, spinous processes, vertebral bodies, and sacroiliac joints (SIJs) were evaluated for FDG accumulation using maximum standardised uptake values (SUVmax ) and FDG scores. Results: SUVmax for ischial tuberosities was significantly higher in patients with PMR than in those with SpA or RA. SUVmax for greater trochanters and spinous processes were significantly higher in patients with PMR than in those with RA ( P <0.001). SUVmax for SIJs was significantly higher in patients with SpA than in those with PMR or RA ( P =0.01).No significant difference in vertebral scores was observed among groups ( P =0.488). Similar results were obtained when each site was evaluated using FDG scores. X-ray findings were consistent with PET/CT findings in 3/15 (20%) patients with sacroiliitis, while magnetic resonance imaging findings were consistent with PET/CT findings in 4/7 (57.1%) patients. Conclusions: PET/CT detection of inflammation in the ischial tuberosities, greater trochanters, and spinous processes discriminated between PMR and RA, but not between SpA and PMR. PET/CT findings for SIJs are useful for distinguishing SpA from RA and PMR and for the early diagnosis of sacroiliitis. Disclosure of Interest: None Declared